Pro JavaScript with MooTools: Learning Advanced JavaScript Programming - Obcena, Mark Joseph A. (Apress, 2012)
This book is about JavaScript as it relates to the MooTools framework. Like any other language, JavaScript’s predictability has a lot to do with the people who code with it. While it is pretty predictable, JavaScript does have some quirks and unique features that might not be apparent at base level. Unfortunately, a lot of us who proudly proclaim to be JavaScript developers don’t take time to learn the language enough to appreciate these quirks and features.